The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1088/1741-2552/aae39d
|View full text |Cite
|
Sign up to set email alerts
|

Long-term recording reliability of liquid crystal polymer µECoG arrays

Abstract: Objective. The clinical use of microsignals recorded over broad cortical regions is largely limited by the chronic reliability of the implanted interfaces. Approach. We evaluated the chronic reliability of novel 61-channel micro-electrocorticographic (μECoG) arrays in rats chronically implanted for over one year and using accelerated aging. Devices were encapsulated with polyimide (PI) or liquid crystal polymer (LCP), and fabricated using commercial manufacturing processes. In vitro failure modes and predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 107 publications
(159 reference statements)
6
69
0
Order By: Relevance
“…The results for the PI/ALD-3/PI film reveal that the impedance and the phase angle remain stable during exposure to PBS, indicating that the barrier was not affected by the soaking environment. (Table 1) [12,44,45]. To the best of our knowledge, the soaking results reported in this paper represent an excellent long-term encapsulation and PI/ALD-3/PI has great potential for the development of long-term implantable medical electronic devices.…”
Section: Eismentioning
confidence: 67%
See 1 more Smart Citation
“…The results for the PI/ALD-3/PI film reveal that the impedance and the phase angle remain stable during exposure to PBS, indicating that the barrier was not affected by the soaking environment. (Table 1) [12,44,45]. To the best of our knowledge, the soaking results reported in this paper represent an excellent long-term encapsulation and PI/ALD-3/PI has great potential for the development of long-term implantable medical electronic devices.…”
Section: Eismentioning
confidence: 67%
“…Minnikanti et al, Woods et al, and Forssell et al have put effort into evaluating the lifetime of barriers Al2O3/parylene C, LCP, and parylene C/TiO2/Al2O/TiO2 at an acceleration temperature (60 °C) in PBS, respectively. These barriers performed well up to a few hundred days under similar acceleration conditions (Table 1) [12,44,45]. To the best of our knowledge, the soaking results reported In a previous paper, we showed that a 16 µm PI (HD2611) has a high WVTR of 4.3 g•m −2 •day −1 while ALD-3 coated on the same thickness polyimide resulted in a significant improvement of WVTR to less than 5 × 10 −4 g•m −2 •day −1 [4].…”
Section: Eismentioning
confidence: 85%
“…First, we collected longitudinal data pertaining to behavioral performance but obtained a single readout of neuronal activity. In light of recent advances in devices for chronic and reliable neurophysiological recordings (Woods et al, 2018), future studies may collect both functional and behavioral data simultaneously over the whole training period to better understand the relationship between neuronal circuit function and performance. Future studies could also help determine whether these measures are correlated with PV expression.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term reliability of the LCP encapsulation, including LCP-based electrode arrays and LCP packaging of electronics, has been demonstrated in the previous studies. These studies suggested that the lifetime of LCP encapsulation, including all the possible water penetration paths, e.g., LCP-LCP adhesion, LCP-metal adhesion, and LCP surface permeation, is estimated to be at least a few years at body temperature [40][41][42][43][44][45][46]. The only interface that has not been addressed in the previous studies is the 4ch/8ch connectors sealed by dental cement.…”
Section: Discussionmentioning
confidence: 99%